Good vibrations: Global processing can increase the pleasantness of touch. Issue 12 (1st December 2016) - Mirams, Laura; Poliakoff, Ellen; Zandstra, Elizabeth H.; Hoeksma, Marco; Thomas, Anna; El-Deredy, Wael
Abstract : Visual–tactile carry-over effects of global/local processing (attention to the whole, versus the details) have been reported under active touch conditions. We investigated whether carry-over effects of global/local processing also occur for passive touch and whether global/local processing has differential effects on affective and discriminative aspects of touch. Participants completed two tactile tasks involving pleasantness rating and discrimination of a set of tactile vibrations before and after completing a version of the Navon task that encouraged a focus on the global ( n  = 30), local ( n  = 30), or both ( n  = 30) features of a series of visual stimuli. In line with previous research suggesting a link between global processing and positive emotion, global processing increased pleasantness ratings of high-frequency (but not low-frequency) tactile vibrations. Local processing did not improve the ability to discriminate between vibrations of different frequencies, however. There was some evidence of a tactile–visual carry-over effect; prior local processing of tactile vibrations reduced global precedence during the Navon task in the control group. We have shown carry-over effects of global versus local processing on passive touch perception. These findings provide further evidence suggesting that a common perceptual mechanism determines processing level across modalities and show for the first time that prior global processing affects the pleasantness of touch.